Translation Of Cultural Terms In The Jambi Province Tourism Booklet - Aprily Herdini Elsa; Dian Mukhlisa; Tira Mariana (English Language, Linguistics, Literature, And Education Journal, 2021)
This research analyzes the Translation of Cultural Terms in The Jambi Province Tourism Booklet entitled Jambi Destination Unlimited Treasures and Guide Book. The objective of this research is to describe kinds, strategies, and types of meaning shifts of the cultural terms in the Jambi province tourism booklet and object in this research are Indonesian and English cultural terms. This research employs descriptive qualitative research. The data of this research is all cultural terms in the Jambi province tourism booklet. The data are classified from categories of cultural terms based on Newmark’s theory, the strategies based on Newmark’s theory, and types of meaning shifts based on Chaer’s theory. The findings of this research show that first there are three categories of cultural terms, they are: ecology (five data), material culture (eleven data), and organization and customs (four data). Based on the categories above, the majority of data comes from the category of material culture. Second, there are six translation strategies found. They are: transference (five data), shift or transposition (two data), descriptive equivalent in (five data), functional equivalent (three data), through-translation (one data), and componential analysis (four data). The majority strategy comes from descriptive equivalent and transference strategies. Third, there are three types of meaning shifts found, they are: widening (seven data), narrowing (eleven data), and total change (two data). That types of meaning shifts are occured in translating the cultural terms in the Jambi province tourism booklet.